1974
DOI: 10.1258/002367774780943814
|View full text |Cite
|
Sign up to set email alerts
|

Sex factors in airborne infection: comparative susceptibility of male and female non-immunized mice to aerosolized Pasteurella multocida

Abstract: 351 SPF OF1 non-immunized mice of both sexes were infected by aerosolized Pasteurella multocida. Female mice were significantly less susceptible to infection than were males of the same age (which were heavier). Males and females of equal bodyweight, but different age, showed no significant difference in susceptibility. The difference at equal ages can be explained by the lower respiratory flow of females. The consequences of these results for experimental studies on atmospheric pollutants are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1980
1980
1980
1980

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The 50% lethal doses of K. pneumoniae DT-S for Slc:ICR mice is less than 102 CFU per lung by aerosol infection and 104 CFU per mouse by intraperitoneal infection (unpublished data), showing that K. pneumoniae DT-S is more virulent by respiratory tract infection. It is well known that various animal variables such as species, strain, sex, age, body weight, and breeding conditions should be considered in establishing experimental infections (3,10,32). In aerosol infection with K. pneumoniae in mice, Ehrlich (7) reported that there were strain differences in susceptibility to infection, though no differences were observed in mortality among animals ranging in age from 6 weeks to 9 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 50% lethal doses of K. pneumoniae DT-S for Slc:ICR mice is less than 102 CFU per lung by aerosol infection and 104 CFU per mouse by intraperitoneal infection (unpublished data), showing that K. pneumoniae DT-S is more virulent by respiratory tract infection. It is well known that various animal variables such as species, strain, sex, age, body weight, and breeding conditions should be considered in establishing experimental infections (3,10,32). In aerosol infection with K. pneumoniae in mice, Ehrlich (7) reported that there were strain differences in susceptibility to infection, though no differences were observed in mortality among animals ranging in age from 6 weeks to 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…Kanamycin sulfate (Takeda Chemical Industries, Ltd., Osaka, Japan), dissolved in sterile 0.85% NaCl, was injected subcutaneously (0.2 ml per mouse) according to the schedules presented in Tables 5 and 6 and Figs. 3 to 5. The minimum inhibitory concentration of kanamycin against K. pneumoniae DT-S by the agar dilution method (33) is 1.56 ,ug/ml.…”
mentioning
confidence: 99%